CLINICAL ANALYSIS OF A PATIENT WITH ANTIPHOSPHOLIPID SYNDROME AND SUB-MASSIVE PULMONARY EMBOLISM - E. N. Krivosheeva; A. L. Komarov; R. M. Shakhnovich; I. S. Fedotchenkov; E. Р. Panchenko («REMEDIUM GROUP» Ltd., 2018)
The article presents a clinical analysis of the patient with a newly developed unprovoked episode of venous thromboembolic events. It discusses the challenges in the diagnosis of pulmonary embolism, the need for thrombolytic therapy in patients with pulmonary arterial thromboembolism of medium risk. The guidelines for diagnosis of antiphospholipid syndrome in accordance with modern principles are provided. It also considers the issues of anticoagulant treatment.